2016
DOI: 10.1080/21641846.2016.1206176
|View full text |Cite
|
Sign up to set email alerts
|

Assessing current functioning as a measure of significant reduction in activity level

Abstract: Background-Myalgic encephalomyelitis (ME) and chronic fatigue syndrome (CFS) have case definitions with varying criteria, but almost all criteria require an individual to have a substantial reduction in activity level. Unfortunately, a consensus has not been reached regarding what constitutes substantial reductions. One measure that has been used to measure substantial reduction is the Medical Outcomes Study Short Form-36 Health Survey (SF-36). [1]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…A decrease in activity level is a cardinal feature of many proposed definitions of CFS/ME, which produces a substantial reduction or impairment in the ability to carry out daily activities of life. In fact, a reduction in activity level of at least 50% below premorbid levels has been reported [ 2 ] Using actigraphy, activity levels during the day were found to be lower in patients than in controls, as has already been reported [ 24 ]. Our results confirm these differences and add that between 12h and 14h, activity did not differ between the groups.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…A decrease in activity level is a cardinal feature of many proposed definitions of CFS/ME, which produces a substantial reduction or impairment in the ability to carry out daily activities of life. In fact, a reduction in activity level of at least 50% below premorbid levels has been reported [ 2 ] Using actigraphy, activity levels during the day were found to be lower in patients than in controls, as has already been reported [ 24 ]. Our results confirm these differences and add that between 12h and 14h, activity did not differ between the groups.…”
Section: Discussionsupporting
confidence: 56%
“…During the course of the illness, CFS/ME patients also experience relapses and partial remissions of the common features which include pathological dysregulation of the neuro-endocrine, immunological, gastrointestinal, autonomic systems with cellular energy metabolism/ion transport impairments of varying onset, duration, frequency and severity, reviewed in [ 1 ]. Symptoms can persist for years, and few patients regain their premorbid level of health or functioning [ 2 ]. The duration of CFS/ME and the potentially debilitating consequences of its symptoms significantly increase the economic burden and establish the condition as a top-level health problem in today’s society [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…All mean measurements during the re-evaluation showed a significant deterioration (P < 0.0001) in comparison to the initial evaluation. Phys F: Physical Functioning scale of the SF-36 questionnaire; %peak VO 2 : peak VO 2 oxygen uptake relative to controls [37]; No of steps: number of steps per day functioning scale of 0.91 [44], suggesting that the use of the physical functioning score is valid with an acceptable sensitivity and specificity. Several studies have shown a decreased peak VO 2 in ME/CFS patients [45].…”
Section: Discussionmentioning
confidence: 99%
“…In the community-based sample the AUC of the physical functioning scale was 0.84 and in the tertiary care sample 0.87. However, another study found an AUC for assessing substantial reductions of the physical functioning scale of 0.91 [45], suggesting that the use of the physical functioning score is valid with an acceptable sensitivity and speci city.…”
Section: Discussionmentioning
confidence: 99%